World Environmental and Water Resources Congress 2012 2012
DOI: 10.1061/9780784412312.036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Initial Abstraction Ratio in SCS-CN Method on Modeling the Impacts of Urbanization on Peak Flows

Abstract: The initial abstraction ratio (λ) used in the SCS-CN method plays an important role in calculation of runoff volume and consequently hydrograph peak. The recommended value for λ in the SCS handbook is 0.2. However, recent studies suggest that λ varies between 0.05 and 0.2, closer to the lower bound. Yet, the SCS recommended value of 0.2 is still being widely used in many hydrologic models. In this study, we explored the effects of variation in λ on simulating urbanization impacts in a coastal Alabama watershed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Noori et al . () and others have discovered that this ratio more accurately predicts runoff from urbanized watersheds than the traditional λ = 0.2 that is used for small agricultural watersheds. Substituting those values into the initial abstraction equation (Equation ), it is determined that I a = 0.01 inches (0.03 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Noori et al . () and others have discovered that this ratio more accurately predicts runoff from urbanized watersheds than the traditional λ = 0.2 that is used for small agricultural watersheds. Substituting those values into the initial abstraction equation (Equation ), it is determined that I a = 0.01 inches (0.03 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Hawkins et al (2002) suggested that Ia/S is not a constant value; rather, it varies between different storms and different basins. Noori et al (2012) found that Ia/S 5 0.05 provides superior results compared to the recommended value of 0.2. Fu et al (2011) analyzed 757 rainfall-runoff events in Shaanxi and Gansu Provinces to quantify the Ia/S, indicating that the average value of Ia/S is 0.08 and the median value is 0.05 in the Loess Plateau of China.…”
Section: Introductionmentioning
confidence: 92%
“…3) Storms satisfying P/S # 0.456 should be excluded and considered as small storms for SCS-CN application (Hawkins et al 1985). The use of smaller events could bias the results toward a larger CN (Woodward et al 2003;Hawkins et al 2009;Noori et al 2012), yet low rainfall events with a high CN bias can be found in essentially every dataset (Mishra et al 2007). This criterion, namely, storms satisfying P/S .…”
Section: ) Rainfall-runoff Events Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using land use (2012), soil and rainfall data, the proposed model was developed, and later calibrated and validated against the observed run-off in 2010 and 2011, respectively. The calibration process also comprised modification of the value of the coefficient of initial abstraction (Bo et al, 2011;Noori, Kalin, Srivastava, & Charlene, 2012;Shi, Chen, Fang, Qin, & Cai, 2009;Yuan, Nie, Mccutcheon, & Taguas, 2014). An acceptable accuracy of 80% in the results was observed during both model calibration and validation.…”
Section: Assessment Of Land Use Changes and Check Dam Impacts On Rumentioning
confidence: 99%